2021
DOI: 10.7717/peerj-cs.316
|View full text |Cite
|
Sign up to set email alerts
|

Researching COVID-19 tracing app acceptance: incorporating theory from the technological acceptance model

Abstract: Background The expansion of the coronavirus pandemic and the extraordinary confinement measures imposed by governments have caused an unprecedented intense and rapid contraction of the global economy. In order to revive the economy, people must be able to move safely, which means that governments must be able to quickly detect positive cases and track their potential contacts. Different alternatives have been suggested for carrying out this tracking process, one of which uses a mobile APP which has already bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
117
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(132 citation statements)
references
References 65 publications
13
117
2
Order By: Relevance
“…The fear factor was tackled in recent studies by [27] as an external factor that affects students' perception of technology during the pandemic. The fear from COVID-19 is manifested in forms such as threat, anxiety, feeling of uncertainty, the risk for loved ones [19,[28][29][30][31][32]. The feeling of fear among students has affected education and changed the platform of teaching from the physical classes to a virtual class by implementing an online platform [33].…”
Section: Perceived Fearmentioning
confidence: 99%
“…The fear factor was tackled in recent studies by [27] as an external factor that affects students' perception of technology during the pandemic. The fear from COVID-19 is manifested in forms such as threat, anxiety, feeling of uncertainty, the risk for loved ones [19,[28][29][30][31][32]. The feeling of fear among students has affected education and changed the platform of teaching from the physical classes to a virtual class by implementing an online platform [33].…”
Section: Perceived Fearmentioning
confidence: 99%
“… 27 An extended TAM was used to find that it is likely citizens would download the app regardless of privacy concerns, and the main factor in this decision was determined to be the perceived usefulness of the app. 28 A similar study used a Health Belief Model, and found that perceived benefits of contact tracing apps were the largest factor for users downloading the app, followed by self-efficacy and perceived barriers. 29 Additionally, a report early in the pandemic suggested public trust and confidence, and technical design choices influencing the privacy and security of the system would contribute largely to app adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the data security category, a typical example of a facilitator and barrier is "perceived trust" and "privacy concern," respectively. For example, Velicia-Martin et al [14] and Walrave et al [15] found that perceived usefulness (a facilitator) and privacy concern (a barrier), respectively, are associated with contact tracing app adoption. Finally, "%Total" indicates the percentage of the total reviewed articles that found a given factor (facilitator or barrier) to be (1) a significant determinant of contact tracing app adoption in quantitative studies involving correlational, regression, and path analyses and/or (2) a noteworthy theme in qualitative studies based on the thematic analysis of participants' comments.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the percentage of study participants (especially nonadopters of contact tracing apps) who are willing to download the app under evaluation may be an indication of how the app may fair in real-life contexts, especially if the facilitators of contact tracing app adoption are prioritized. In addition, we will be looking at the levels of perception of key facilitators (eg, perceived usefulness [14]) and barriers (eg, privacy concern [15]) associated with contact tracing app adoption. For example, in a given study, "Did the participants perceive the contact tracing app described or prototyped as useful, trustworthy, etc?"…”
Section: Outcomes and Prioritizationmentioning
confidence: 99%